2021
DOI: 10.1093/nar/gkab1231
|View full text |Cite
|
Sign up to set email alerts
|

Early rRNA processing is a stress-dependent regulatory event whose inhibition maintains nucleolar integrity

Abstract: The production of ribosomes is an energy-intensive process owing to the intricacy of these massive macromolecular machines. Each human ribosome contains 80 ribosomal proteins and four non-coding RNAs. Accurate assembly requires precise regulation of protein and RNA subunits. In response to stress, the integrated stress response (ISR) rapidly inhibits global translation. How rRNA is coordinately regulated with the rapid inhibition of ribosomal protein synthesis is not known. Here, we show that stress specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 89 publications
3
19
0
Order By: Relevance
“…Interestingly, a recent study demonstrated defects in 45S rRNA processing upon sodium arsenite exposure (40). We speculate that the accumulation of rRNA in cytoplasmic granules distinct from stress granules and P-bodies may be related to the elimination of misprocessed forms generated during oxidative stress.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, a recent study demonstrated defects in 45S rRNA processing upon sodium arsenite exposure (40). We speculate that the accumulation of rRNA in cytoplasmic granules distinct from stress granules and P-bodies may be related to the elimination of misprocessed forms generated during oxidative stress.…”
Section: Discussionmentioning
confidence: 71%
“…Further, we find that granule formation is sensitive to the RNA Pol I inhibitor ActD but largely insensitive to the RNA Pol II inhibitor α-amanitin, suggesting that granules contain rRNA. Interestingly, a recent study demonstrated defects in 45S rRNA processing upon sodium arsenite exposure(40). We speculate that the accumulation of rRNA in cytoplasmic granules distinct from stress granules and P-bodies may be related to the elimination of misprocessed forms generated during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated defects in 45S rRNA processing upon sodium arsenite exposure. 29 We speculate that the accumulation of rRNA in cytoplasmic granules distinct from stress granules and P-bodies may be related to the elimination of misprocessed forms generated during oxidative stress. The accumulation of DDX6 in these structures is intriguing as DDX6 has been implicated in P-body assembly, mRNA decay, and translational repression 26,30 but to the best of our knowledge is not known to interact with rRNA.…”
Section: ■ Discussionmentioning
confidence: 88%
“…The nucleolus possesses numerous functions, including ribosome biogenesis, nuclear organization, regulation of global gene expression, and energy metabolism (Cerqueira and Lemos, 2019). It also responds to multiple stresses, such as hypoxia, pH fluctuations, redox stress, DNA damage, or proteasome inhibition, and acts as a protein quality control center that can mitigate heat shock-induced proteotoxicity (Mekhail et al, 2005; Latonen et al, 2011; Audas et al, 2012; Yang et al, 2016; Lindström et al, 2018; Alberti and Carra, 2019; Azkanaz et al, 2019; Frottin et al, 2019; Mediani et al, 2019; Szaflarski et al, 2022). In our studies, we focused on the latter function.…”
Section: Discussionmentioning
confidence: 99%